KESEDIAAN MEMBAYAR PETANI KOPI UNTUK PERBAIKAN LINGKUNGAN - Prasmatiwi, Fembriarti Erry; Irham, Irham; Suryantini, Any; Jamhari, Jamhari (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
This study aims were, first to measure the level of farmersâ willingness to pay the external cost to improve the environment and second, examine the determinant factors. The experiment was conducted in District Sumberjaya and Sekincau, West Lampung District during June-October 2009. Contingent Valuation Method (CVM) was used to answer the first purpose, while ordinal logit regression analysis was used to answer the second purpose. Factors of farmland area, land productivity, household income, educational level, number of family labor, and knowledge of farmers about the benefits of forests had positive influence on WTP while distance of farmersâ house to the forest had negative influence. The increase of WTP was needed to reduce environmental damage due to forest conversion to coffee plantation; moreover, environment improvement hopefully could restore the function of forest where coffee trees were planted.